A European perspective of phylogenomics, sublineages, geographical distribution, epidemiology, and mutational landscape of mpox virus: Emergence pattern may help to fight the next public health emergency in Europe - Chiranjib Chakraborty; Manojit Bhattacharya; G. Saikumar; Abdulrahman Alshammari; Metab Alharbi; Sang-Soo Lee; Kuldeep Dhama (Journal of Infection and Public Health, 2023)
Background: The 2022 outbreak of the mpox virus (previously monkeypox virus, MPXV) in non-epidemic regions has created a global issue. The emergence of MPXV was first reported in Europe, which was described as the MPXV epicenter, however, no reports are available to illustrate its outbreak patterns in Europe. Methods: The study used numerous in silico and statistical methods to analyze hMPXV1 in European countries. Here, we used different bioinformatics servers and software to evaluate the spread of hMPXV1 in European countries. For analysis, we use various advanced servers like Nextstrain, Taxonium, MpoxSpectrum, etc. Similarly, for the statistical model, we used PAST software. Results: The phylogenetic tree was depicted to illustrate the origin and evolution of hMPXV1 using vas number of genome sequences (n = 675). We found several sublineages in Europe, indicating microevolution. The scatter plot reveals the clustering patterns of the newly developed lineages in Europe. We developed statistical models for the monthly total relative frequency counts of these sublineages. The epidemiology of MPX in Europe was examined in an attempt to capture the epidemiological pattern, total cases, and deaths. Our Study noted the highest number of cases was in Spain (7500 cases) and the second-highest in France (4114 cases). The third highest number of cases was in the UK (3730 cases), which was very similar to Germany (3677 cases). Finally, we noted the mutational landscape throughout European genomes. Significant mutations were observed at the nucleotide and protein levels. We identified several unique homoplastic mutations in Europe. Conclusion: This study reveals several essential aspects of the European outbreak. It might help to eradicate the virus in Europe, assist in strategy formation to fight against the virus, and support working against the next public health emergency in Europe.